If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -1b)(6a + -7b) = 0 Multiply (5a + -1b) * (6a + -7b) (5a * (6a + -7b) + -1b * (6a + -7b)) = 0 ((6a * 5a + -7b * 5a) + -1b * (6a + -7b)) = 0 Reorder the terms: ((-35ab + 30a2) + -1b * (6a + -7b)) = 0 ((-35ab + 30a2) + -1b * (6a + -7b)) = 0 (-35ab + 30a2 + (6a * -1b + -7b * -1b)) = 0 (-35ab + 30a2 + (-6ab + 7b2)) = 0 Reorder the terms: (-35ab + -6ab + 30a2 + 7b2) = 0 Combine like terms: -35ab + -6ab = -41ab (-41ab + 30a2 + 7b2) = 0 Solving -41ab + 30a2 + 7b2 = 0 Solving for variable 'a'. Factor a trinomial. (6a + -7b)(5a + -1b) = 0Subproblem 1
Set the factor '(6a + -7b)' equal to zero and attempt to solve: Simplifying 6a + -7b = 0 Solving 6a + -7b = 0 Move all terms containing a to the left, all other terms to the right. Add '7b' to each side of the equation. 6a + -7b + 7b = 0 + 7b Combine like terms: -7b + 7b = 0 6a + 0 = 0 + 7b 6a = 0 + 7b Remove the zero: 6a = 7b Divide each side by '6'. a = 1.166666667b Simplifying a = 1.166666667bSubproblem 2
Set the factor '(5a + -1b)' equal to zero and attempt to solve: Simplifying 5a + -1b = 0 Solving 5a + -1b = 0 Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. 5a + -1b + b = 0 + b Combine like terms: -1b + b = 0 5a + 0 = 0 + b 5a = 0 + b Remove the zero: 5a = b Divide each side by '5'. a = 0.2b Simplifying a = 0.2bSolution
a = {1.166666667b, 0.2b}
| X-23=65 | | s=2(3.14)(r)(l) | | M-9x=0 | | 8=8v-y(v+8) | | 1-5(x+15)= | | -6w+12=6w-8 | | 7x-16=6x-19 | | 4p+3p-7=2p+7 | | 2h-7=-3(h-1) | | 8x-2=-1(9-7x) | | 1-8b-5=-12 | | (2h+3)(2+3h+4)= | | 2n-3=3n+31 | | 8(t-5)+4t=6(2t+5)-12 | | 2x-18=X+24 | | 6y+3+2(3y-12)= | | 4n+7=4n-3 | | 3-0*2+1= | | 33x-16-17x=4(4x-5)+4 | | 3-0*2+1=0 | | 150+2x=5x | | 2x+13=x^2+49 | | 3a+b+c=12c | | a(5x-10)=10x-b | | x(x+12)=x^2+12 | | x+(x-8)=32 | | 13+y=34 | | 8r-2=-9+7x | | 2x=x^2+36 | | 3x+9-7(x+1)=4x+5 | | -2(p-1)=1 | | 150+5x=2x |